2020
DOI: 10.1101/2020.02.02.928283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermogenic hydrocarbons fuel a redox stratified subseafloor microbiome in deep sea cold seep sediments

Abstract: 20At marine cold seeps, gaseous and liquid hydrocarbons migrate from deep subsurface 21 origins to the sediment-water interface. Cold seep sediments are known to host 22CoM reductase pathway), longer-chain alkanes (fumarate addition pathway), and 35 aromatic hydrocarbons (fumarate addition and subsequent benzoyl-CoA pathways), 36 including novel lineages within Methanosarcinales and Chloroflexi. Geochemical 37 profiling demonstrated that hydrocarbon substrates are abundant in this location, 38 thermogenic in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 93 publications
(157 reference statements)
0
14
0
Order By: Relevance
“…The taxonomy of each MAG was temporally assigned using GTDB-Tk [102] (GTDB R04-RS89 database). The relative abundance of each MAGs was calculated with CoverM (https://github.com/wwood/CoverM) as previously described [103]. The taxonomic classification, size, completeness, contamination, strain heterogeneity, and N50 of recovered MAGs are summarized in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…The taxonomy of each MAG was temporally assigned using GTDB-Tk [102] (GTDB R04-RS89 database). The relative abundance of each MAGs was calculated with CoverM (https://github.com/wwood/CoverM) as previously described [103]. The taxonomic classification, size, completeness, contamination, strain heterogeneity, and N50 of recovered MAGs are summarized in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…Except for EGM and SB, metagenomic datasets along with metadata were downloaded from NCBI Sequence Read Archive and NCBI BioSample databases (https://www.ncbi.nlm.nih.gov). Sample collection and DNA sequencing of samples from EGM and SB are described in detail elsewhere 23,24 .…”
Section: Collection Of Metagenomic Datasets For Deep Sea Cold Seepsmentioning
confidence: 99%
“…Apart from well-documented lineages of Deltaproteobacteria and Archaeoglobi [6,21], faeA genes are reported here as also occurring in the class Dehalococcoidia within the phylum Chloro exi, the class Thermoplasmata within the phylum Euryarchaeota, and within the Asgard superphylum (Lokiarchaeota, Thorarchaeota, and Heimdallarchaeota). Current knowledge about archaea involved in anaerobic hydrocarbon degradation focuses mainly on oxidation of methane and other short alkane gases using methyl-CoM reductase or methyl-CoM reductase-like enzymes [25,44,45]. New archaeal diversity presented here for the degradation of longer alkanes opens up a wider perspective on the evolution and expansion of hydrocarbon-oxidizing pathways throughout the archaeal domain.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic analysis of a different oil reservoir revealed an Archaeoglobus encoding and expressing the alpha subunit of alkylsuccinate synthase (AssA) [22]. Investigations of marine sediments from cold seeps, hydrothermal elds and deep subsurface layers using genome-resolved metagenomics have revealed that hydrocarbon oxidizers that use fumarate addition might have an even wider phylogenetic distribution [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%